A novel electrochemical sensor for the determination of cadmium ions based on nitrogen-enriched carbon modified electrode - S. Ghrkhlari; Fatemeh Ahour; S. Keshipour (Scientific Reports)
Abstract In the present work, nitrogen-doped carbon was synthesized starting from a chitosan/urea mixture and immobilized at the surface of a bare glassy carbon electrode to detect Cd(II) ions using differential pulse-anodic stripping voltammetry method (DP-ASV). The synthesized nitrogen-doped carbon showed a significant potential for determining Cd(II) ions. Doping carbon with nitrogen atoms gives a structure with increased valence band energy, leading to acceleration of the electron transfer by creating an interaction of nitrogen’s free electrons with Cd(II), which subsequently increases the peak current value. After the characterization of nitrogen-doped carbon by various methods, cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were used to study the prepared sensor’s electrochemical behavior. Under optimal conditions, the proposed sensor has a linear response of 3.0 to 150 nM and its detection limit is 2.0 nM. This sensor can analyze Cd(II) in tap and river water as real samples.